Cytochrome P450 CYP2B6*6 distribution among Congolese individuals with HIV, Tuberculosis and Malaria infection. (May 2019) - Peko, Simon Marie; Gueye, Nerly Shirère Gampio; Vouvoungui, Christevy; Koukouikila-Koussounda, Félix; Kobawila, Simon Charles; Nderu, David; Velavan, Thirumalaisamy P.; Ntoumi, Francine
Highlights: CYP2B6 c.516G>T modulates bioavailability of drugs used to treat HIV, Malaria and TB. CYP2B6 c.516G>T is considered to be an independent predictor of Efavirenz plasma concentrations in HIV-infected patients. High frequency of CYP2B6 c.516G>T genotypes that contribute to intermediate (55%) and poor response (28%) to TB/HIV treatment. Abstract: Background: The cytochrome P450 CYP2B6*6 ( CYP2B6 c.516G>T; rs3745274) is one of the genetic factors that alters the drug metabolism in antimalarial, antiretroviral and TB first-line drugs. In Central African populations, the distribution of the CYP2B6*6 variant is poorly documented. This study investigated the distribution of CYP2B6 c.516G>T variant among Congolese individuals. Methods: A total of 418 patients with HIV-1 mono-infection, HIV-1 and Tuberculosis coinfection and symptomatic P. falciparum malaria were genotyped for the CYP2B6 c.516G>T SNP using Restriction Fragment Length Polymorphism (RFLP). The allele frequencies and genotype distributions were determined. Results: The CYP2B6 c. 516G>T was successfully analysed in 69% (288/418) of the study participants. Among the investigated individuals, the distribution of the major allele CYP2B6* G was 45% and the minor CYP2B6* T allele was 55%. Significant differences in genotype distribution were also observed among the studied individuals. The CYP2B6* GG (rapid metabolizer) genotype was observed in 17% (49/288) followed by CYP2B6* GT (intermediate metabolizer) 55% (159/288) and CYP2B6* TT (poor metabolizers) 28% (80/288). Conclusion: This study contributes to increasing understanding on population pharmacogenetics and may help policy makers regulate treatment guidelines in the Congolese population with a high burden of HIV, Malaria and TB.